The practice of authentic PLCs : a guide to effective teacher teams - Venables, Daniel R. (Corwin Press, 2011)
Provides numerous strategies, activities, exercises, and guidance for PLC (Professional Learning Community) leaders, including FAQs and a troubleshooting guide to common obstacles.